Biostatistics for the Health Sciences - R. Clifford Blair (Pearson, 2008)
This book provides a solid foundation in introductory biostatistics with up-to-date methods, lucid explanations, and a modern approach. Explains commonly used biostatistical methods, such as odds and risk ratios, and Fisher's exact test, in a clear and thorough manner. Introduces equivalence testing in a variety of research settings. Presents nonparametric methods in a modern light, couched in the broader context of permutation-based methods. Provides real-world data with case studies consisting of synopses of published research. Provides step-by-step solutions to exercises, along with pertinent equations used in obtaining the solution and page numbers of relevant discussions.